River Transportation Terminal Design - Amin, Samsuddin; Amri, Nurmaida; ., Idawarni; Yahya, M.; Syarif, Edward; Nadjmi, Nurul (Faculty of Engineering UNHAS, 2023)
This article discusses the importance of developing transportation infrastructure on the banks of the river to support the activities of residents in riverside settlements in the context of utilizing the river as an alternative mode of transportation in addition to land transportation modes. The design of river transportation terminals can be a solution to support the activities of residents living in riverside settlements in the context of empowerment in addition to strengthening the local identity of the riverside area. The purpose of this Community Service is to increase the economic empowerment of the community, especially the people who live on the side of the Walanae River, Lompulle Village, Ganra District, Soppeng Regency through the use of the Walanae River as a means of water transportation in order to facilitate the movement and movement of goods through the river to become a link to several areas which are the Walanae Watershed (DAS). The utilization of the river can be optimized not only through the use of the river as an alternative means of transportation, but also as a water tourism object which in the end is expected to create new livelihoods for the community from the tourism aspect through the provision of souvenirs and the use of residents' homes as homestays as supporting regional tourism in a broader context.The method of implementing activities formulated by the Community Service Team of the Department of Architecture, Faculty of Engineering, Hasanuddin University starts from field observation activities followed by analyzing the potential and existing problems related to the River Transportation Terminal development plan at the service location. The results of the implementation of the activity showed enthusiasm, as well as a significant level of understanding and acceptance with a significance figure of 62,16% from 18,92% before the activity to 81,08% after the implementation of the activity.